The genus Dyella spp. bacteremia from hemodialysis blood culture: a case report - Siribamrungwong, Monchai; Jearakitiwanich, Kwanchon (Archives of Allied Health Sciences, 2025)
This study presents a patient identified to have Dyella spp., a rare genus of bacteria, bacteremia. Dyella spp. cannot be identified through biochemical testing methods. At present, Matrix-assisted laser desorption/ionization is applied to differentiate the types of microbes. However, there is a limitation in distinguishing the specific type of bacteria because of the limitation of library databases. The 16S rRNA sequencing is crucial for differentiating the rare genus of bacteria that are improbable to recognize by mass spectrometry technique. This report highlights the discovery of Dyella spp. in patient blood culture, emphasizing the challenges in identification by Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometer (MALDI-TOF MS), an ordinary technique. The instruction provided in this report aims to improve the application of this high-technology machine to accurately differentiate the rare genus of bacteria, ultimately enhancing patient care and treatment outcomes.